1996
DOI: 10.1177/088307389601100202
|View full text |Cite
|
Sign up to set email alerts
|

Topical Review: Baclofen in the Treatment of Cerebral Palsy

Abstract: Baclofen, a gamma-aminobutyric acid agonist, acts at the spinal cord level to impede the release of excitatory neurotransmitters that cause spasticity. Oral baclofen improves cerebral spasticity mildly, but its activity is limited because of its poor lipid solubility. Cerebrospinal fluid baclofen levels after intrathecal administration are many times higher than those achieved after oral administration. Continuous intrathecal baclofen infusion has been used to treat cerebral spasticity in two patient groups: i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(88 citation statements)
references
References 29 publications
0
88
0
Order By: Relevance
“…This has not been previously reported, probably because most tests used 100 mg as maximal dose. Albright 28 considers that 85% of the patients respond to doses between 50 and 100 mg. Test doses above 100 mg have been considered to be dangerous and useless because response to such doses would imply treatment doses superior to 1000 mg. 6 This has not been our experience. We never observed side effects in the patients tested with doses superior to 100 mg and follow-up doses never exceeded 1000 mg/day.…”
Section: Bolus Test Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This has not been previously reported, probably because most tests used 100 mg as maximal dose. Albright 28 considers that 85% of the patients respond to doses between 50 and 100 mg. Test doses above 100 mg have been considered to be dangerous and useless because response to such doses would imply treatment doses superior to 1000 mg. 6 This has not been our experience. We never observed side effects in the patients tested with doses superior to 100 mg and follow-up doses never exceeded 1000 mg/day.…”
Section: Bolus Test Proceduresmentioning
confidence: 99%
“…3,43 The use of refill kits, including bacteria filters, has decreased their incidence. 37,44 The perioperative antibioprophylaxis, suggested by some authors, 28,29 is not yet established. Besides classical treatment (antibiotics, removal, and then replacement of the pump), some authors have reported new approaches with instillation of appropriate antibiotics into the reservoir 44 and intrathecal perfusion of antibiotics while continuing ITB, 45 with success.…”
Section: Pharmacological Side Effectsmentioning
confidence: 99%
“…Often, the daily doses must be increased over time. 23,24,29 lntrathecal administration of baclofen can o er many advantages for patients who experience intolerable side e ects at e ective doses of oral medications. Delivering the medication directly to the target site means that cerebrospinal uid levels can be much higher than with oral administration which crosses the blood-brain barrier poorly.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most common in current use are intrathecal baclofen [6][7][8][9] and intramuscular botox. More recently deep brain stimulation has been used for dystonia.…”
Section: Conventional Interventionsmentioning
confidence: 99%